2007
DOI: 10.1097/hjh.0b013e32826f49a3
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of baroreceptor control of cerebral blood flow velocity at a simulated altitude of 5000 m

Abstract: During acute exposure to high altitude, cerebral blood flow is still modulated by the autonomic nervous system through the baroreflex, whose sensitivity is not affected by changes in CO2 and oxygen saturation levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…To minimize respiratory-related modulation of heart rate, the 5-s pulses of neck suction were delivered to the carotid sinus during controlled breathing. Specifically, participants were instructed to breathe along to a metronome set at ~15 breaths/min, consistent with work published previously (23,26,39,49). Respiration was assessed by use of a Piezo Respiratory Belt Transducer (MLT1132; ADInstruments, Colorado Springs, CO).…”
Section: Methodsmentioning
confidence: 99%
“…To minimize respiratory-related modulation of heart rate, the 5-s pulses of neck suction were delivered to the carotid sinus during controlled breathing. Specifically, participants were instructed to breathe along to a metronome set at ~15 breaths/min, consistent with work published previously (23,26,39,49). Respiration was assessed by use of a Piezo Respiratory Belt Transducer (MLT1132; ADInstruments, Colorado Springs, CO).…”
Section: Methodsmentioning
confidence: 99%
“…The interpretation of this phase angle is controversial: while some investigators consider it a marker of dynamic autoregulation [18], others have previously suggested that it may instead depend upon the autonomic control of the cerebral vessels [19,36]. A larger phase angle implicates the intervention of some modulating factor (either intrinsic to the vessels or with the implication of the autonomic nervous system), whereas a smaller angle indicates a more passive transmission between main arteries and blood vessels.…”
Section: Autonomic Disturbances In Copd Patientsmentioning
confidence: 99%
“…Marple [45] and applied in many previous studies assessing PA as a parameter of cerebral autoregulation [10,24,25,29,30,40,43,46].…”
Section: Methodsmentioning
confidence: 99%